Grammatisches Problembewusstsein Als Regulativ Für Angemessene Sprachbeurteilung . Das Beispiel Der Griechischen Negation Und 2PETR - Kraus, Thomas J. (Filología neotestamentaria, 2001)
Language and style are the inevitable starting points for evaluating and interpreting an individual text. Thus, a profound orientation in the field of Greek grammar has a regulating effect on all kinds of judgement of the character of a NT text. With the help of the use of the Greek Negation in 2Peter and the interpretation of 2:10 (pa=j ... ou0 ...) as a semitism the benefit of a continuous involvement in the usage and development of the Greek language can be demonstrated. Moreover, such an involvement will help to unveil other features of an author's capacity to express himself and contribute to an overall assessment of a specific text.